Intense starbursts at z∼5: First significant stellar mass assembly in the progenitors of present-day spheroids - Verma, A; Lehnert, M; Schreiber, N; Bremer, M; Douglas, L (2007)
High redshift galaxies play a key role in our developing understanding of galaxy formation and evolution. Since such galaxies are being studied within a Gyr of the big bang, they provide a unique probe of the physics of one of the first generations of large-scale star-formation. We have performed a complete statistical study of the physical properties of a robust sample of z∼5 UV luminous galaxies selected using the Lyman-break technique. The characteristic properties of this sample differ from LBGs at z∼3 of comparable luminosity in that they are a factor of ten less massive (∼few109 M) and the majority (∼70%) are considerably younger (<100Myr). Our results support no more than a modest decline in the global star formation rate density at high redshifts and suggest that ∼1% of the stellar mass density of the universe had already assembled at z∼5. The constraint derived for the latter is affected by their young ages and short duty cycles which imply existing z∼5 LBG samples may be highly incomplete. These intense starbursts have high unobscured star formation rate surface densities (∼100s M yr1 kpc2), suggesting they drive outflows and winds that enrich the intra- and inter-galactic media with metals. These properties imply that the majority of z∼5 LBGs are in formation meaning that most of their star-formation has likely occurred during the last few crossing times. They are experiencing their first (few) generations of large-scale star formation and are accumulating their first significant stellar mass. As such, z∼5 LBGs are the likely progenitors of the spheroidal components of present-day massive galaxies (supported by their high stellar mass surface densities and their core phase-space densities). © 2008 International Astronomical Union.